Modeling the effect of loving pedagogy dispositions and teacher self-efficacy on teacher burnout - Chen, Shuya (Frontiers in Psychology, 2023)
Introduction Foreign language teaching is a demanding and challenging profession, and teacher burnout is a common issue in this field. There is a growing research interest in exploring the factors that can protect teachers from burnout and promote their well-being, as well as their effectiveness in the classroom. One such factor might be loving pedagogy, which refers to a teacher’s positive and compassionate attitudes and behaviors toward their students. This study aimed to examine the association between Dispositions toward Loving Pedagogy (DTLP), teacher self-efficacy, and teacher burnout among a sample of Chinese English as a foreign language (EFL) teachers. Methods The participants included 428 English teachers from various parts of China. Data on the three constructs were gathered using an electronic survey which comprised three valid questionnaires for these variables. Structural equation modeling (SEM) was used to test the hypothesized relations among the latent constructs. Results The results indicated that loving pedagogy dispositions negatively affected teacher burnout and that teacher self-efficacy mediated the effect of loving pedagogy on burnout. More precisely, higher levels of loving pedagogy were associated with greater levels of teacher self-efficacy, which is in turn negatively affected teacher burnout. Discussion These outcomes shed more light on the importance of loving pedagogy dispositions for teachers’ mental health and well-being. The findings have implications for theory and practice, as they suggest that fostering loving pedagogy dispositions among teachers can help prevent burnout and promote their well-being. Teacher training programs could integrate this construct into their curricula to support teachers in developing these attitudes and behaviors. Additionally, future research could explore ways to enhance loving pedagogy and self-efficacy among teachers and assess their impact on teacher well-being and effectiveness.